Halophilic Archaea Mediate the Formation of Proto-Dolomite in Solutions With Various Sulfate Concentrations and Salinities - Qiu, Xuan; Yao, Yancheng; Wang, Hongmei; Shen, Anjiang; Zhang, Jie (Frontiers in Microbiology, 2019)
In the past several decades, sulfate concentration and salinity have been considered to be the two essential hydrochemical factors in the formation of dolomite, yet arguments against this hypothesis have existed simultaneously. To clarify the effects of sulfate concentration and salinity in the mineralization of dolomite, we conducted experiments on dolomite precipitation mediated by a halophilic archaeon, Natrinema sp. J7-1with various sulfate concentrations and salinities. This strain was cultured in a series of Modified Growth Media (MGM) with salinities of ¬¬¬140‰, 200‰ and 280‰. Cells in the post-log phase were harvested and used to mediate the formation of dolomite in solutions with various sulfate concentrations of 0 mM, 3 mM, 29.8 mM and 100 mM and salinities of 140‰, 200‰ and 280‰. X-ray Diffraction (XRD) spectra showed that proto-dolomite, monohydrocalcite and aragonite formed in samples with cells, yet only aragonite was detected in samples without cells. Proto-dolomite was found in all biotic samples, regardless of the variation in salinity and sulfate concentration. Moreover, the relative abundances of proto-dolomite in the precipitates were positively correlated with the salinities of the media but were uncorrelated with the sulfate concentrations of the solutions. Scanning Electronic Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS) results showed that all the proto-dolomites were sphere or sphere aggregates with a mole ratio of Mg/Ca close to 1.0. No obvious variations in morphology and Mg/Ca were found among samples with various sulfate concentrations or salinities. This work reveals that a variation of sulfate concentration in solution (from 0 mM to 100 mM) does not affect the formation of dolomite mediated by halophilic archaea, but an increase of salinity (from 140‰ to 280‰) enhances this process. Our results indicate that under natural conditions, an increase in salinity may be more significant than the decrease of sulfates in microbe-mediated dolomite formation.